Dark Reduction Drives Evasion of Mercury From the Ocean - Lamborg, Carl H.; Hansel, Colleen M.; Bowman, Katlin L.; Voelker, Bettina M.; Marsico, Ryan M.; Oldham, Veronique E.; Swarr, Gretchen J.; Zhang, Tong; Ganguli, Priya M. (Frontiers in Environmental Chemistry, 2021)
Much of the surface water of the ocean is supersaturated in elemental mercury (Hg0) with respect to the atmosphere, leading to sea-to-air transfer or evasion. This flux is large, and nearly balances inputs from the atmosphere, rivers and hydrothermal vents. While the photochemical production of Hg0 from ionic and methylated mercury is reasonably well studied and can produce Hg0 at fairly high rates, there is also abundant Hg0 in aphotic waters, indicating that other important formation pathways exist. Here, we present results of gross reduction rate measurements, depth profiles and diel cycling studies to argue that dark reduction of Hg2+ is also capable of sustaining Hg0 concentrations in the open ocean mixed layer. In locations where vertical mixing is deep enough relative to the vertical penetration of UV-B and photosynthetically active radiation (the principal forms of light involved in abiotic and biotic Hg photoreduction), dark reduction will contribute the majority of Hg0 produced in the surface ocean mixed layer. Our measurements and modeling suggest that these conditions are met nearly everywhere except at high latitudes during local summer. Furthermore, the residence time of Hg0 in the mixed layer with respect to evasion is longer than that of redox, a situation that allows dark reduction-oxidation to effectively set the steady-state ratio of Hg0 to Hg2+ in surface waters. The nature of these dark redox reactions in the ocean was not resolved by this study, but our experiments suggest a likely mechanism or mechanisms involving enzymes and/or important redox agents such as reactive oxygen species and manganese(III).